The ABC of moral development: an attachment approach to moral judgment - Govrin, Aner (Frontiers in Psychology, 2014)
The etiology of moral judgment and its connection to early development as with other cognitive faculties is likely complex. Because research is limited, the causative and contributory factors to the development of moral judgment in pre verbal infants are unclear. However, there is emerging evidence from studies within both infant research and moral psychology that may contribute to our understanding of the early development of moral judgments. This proposed model synthesizes these findings to generate an overarching, yet preliminary, model of the process that appears to contribute to the development of moral judgment in the first year of life. I will propose that through early interactions with the caregiver the child acquires an internal representation of a system of rules that determine how right/wrong judgments are to be construed, used, and understood. By breaking moral situations down into their defining features, the attachment model of moral judgment outlines a framework for a universal moral faculty based on a universal, innate, deep structure that appears uniformly in the structure of almost all moral judgments regardless of their content. The implications of the model for our understanding of innateness, universal morality, and the representations of moral situations are discussed.